Hey Yang, where's my thousand bucks? : and other true stories of staggering depth - Yang, Andrew, 1975- (Akashic Books, Ltd., 2026)
"In this frank, often hilarious collection of true stories, political trailblazer Andrew Yang examines America's breakdown through the lens of his unexpected journey from entrepreneur to presidential candidate. Part political memoir, part comedy, and part interior monologue, Hey Yang, Where's My Thousand Bucks? captures the man's unique ability to make complex ideas accessible and entertaining. In a world of bitter division and endless outrage," says Yang, "this book is my attempt to break through the noise--with humor, honesty, and heart . . . Think of it as an insider's guide to smiling during crazy times." For anyone frustrated with traditional political narratives, curious about the human behind the headlines, or simply looking for a smart, laugh-out-loud exploration of trying to improve life in America, this book promises to enlighten, entertain, and inspire. It's more than a memoir, it's a blueprint for generating optimism in an extremely challenging era." -- Provided by publisher.